1988
DOI: 10.1111/j.1600-0412.1988.tb07817.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of Vagina and Uterus

Abstract: Agenesia of the Müllerian system is a congenital syndrome seldom seen in siblings. This report concerns two sisters with the syndrome. In one of them, the vagina was successfully reconstructed, and the other is awaiting the same operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, retrospective analyses of maternal pregnancy histories failed to identify any association between the syndrome and drug use, illness or exposure to known teratogens (Morcel et al, 2007). Several familial occurrences (Griffin et al, 1976;Jones and Mermut, 1972;Kvint and Wilhelmsson, 1988;Tiker et al, 2000) and linked malformations in relatives (Wottgen et al, 2008) suggested that it might be a genetic defect. Because MRKH patients are infertile, linkage analysis cannot be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…However, retrospective analyses of maternal pregnancy histories failed to identify any association between the syndrome and drug use, illness or exposure to known teratogens (Morcel et al, 2007). Several familial occurrences (Griffin et al, 1976;Jones and Mermut, 1972;Kvint and Wilhelmsson, 1988;Tiker et al, 2000) and linked malformations in relatives (Wottgen et al, 2008) suggested that it might be a genetic defect. Because MRKH patients are infertile, linkage analysis cannot be carried out.…”
Section: Discussionmentioning
confidence: 99%